Tinjauan Sosial-Ekonomi Sinergi Pembangunan Jalan Tol dan Jalan Kereta Api di Pulau Jawa - Wiryawan, Bangkit Aditya; Sudjatmiko, Bambang (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2009)
The construction of highway and railroad as modes of transportation in Java Island has social economic implications. Each of them has different characteristic taht must be suited with local-regional needs. Nonetheless, Indonesia has been experiencing imbalance development of public transportation for the last 30 years. Since 1970's the emphasis of transportation development were mainly on highway road, leaving railroad development behind until 2007 when the government issued Law 23/2007. This underlines the research problem in this paper which uses quantitative methodology in data analyzing. The main goal of this paper is to look the benefit of each transportation modes, and furthermore in finding the posibility of highway road and railroad synergism as the effecient strategy in supporting the development of Java Island.